Microstructure Characteristics of Inconel 625 Superalloy Manufactured by Selective Laser Melting - Li, Shuai; Wei, Qingsong; Shi, Yusheng; Zhu, Zicheng; Zhang, Danqing (Journal of materials science & technology, 2015)
Selective laser melting （SLM）, an additive manufacturing process, is capable of manufacturing metallic parts with complex shapes directly from computer-aided design （CAD） models. SLM parts are created on a layer-by-layer manner, making it more flexible than traditional material processing techniques, in this paper, Inconel 625 alloy, a widely used material in the aerospace industry, were chosen as the build material. Scanning electron microscopy （SEM）, electron back scattering diffraction （EBSD） and X-ray diffraction （XRD） analysis techniques were employed to analyze its microstructure. It was observed that the molten pool was composed of elongated columnar crystal, Due to the rapid cooling speed, the primary dendrite arm space was approximately 0.5 μm and the hardness of SLM state was very high （343 HV）. The inverse pole figure （IPF） indicated that the growing orientation of the most grains was 〈001〉 due to the epitaxial growth and heat conduction. The XRD results revealed that the austenite structure with large lattice distortion was fully formed. No carbides or precipitated phases were found. After heat treatment the grains grew into two microstructures with distinct morphological characters, namely, rectangular grains and limited in the molten pool, and equiaxed grains along the molten boundaries. Upon experiencing the heat treatment, MC carbides with triangular shapes gradually precipitated. The results also identified that a large number of zigzag grain boundaries were formed. In this study, the grain formation and microstructure, and the laws of the molten pool evolution were also analyzed and discussed,